Experimental and Numerical Behavior of Basalt Fiber Reinforced Short Concrete Columns Under Axial Loading - H. Mohammed, Dhiyaa; M. Jabbar, Adil; A. Hasan , Qais (Periodica Polytechnica Civil Engineering, 2024)
This paper presents experimental and numerical investigations to reveal effecting of incorporating basalt fibers into a concrete matrix on the structural behavior and loading capacity of axially loaded short columns. Six volume fractions of chopped basalt fibers are added to the same concrete mixture to prepare six identically reinforced columns. The results illustrate that the bonding forces between microfilaments and matrix increase to provide good internal confinement for concrete ingredients, which enhances compressive strength and column loading capacity. The 0.3 % basalt fiber awarded the best compressive strength, while 0.15 % and 0.3 % awarded the best load capacity to the column. The Addition of basalt fibers delays cracking to increase the cracking load by about 50 % more than no fiber column, which indicates that it needs more energy to overcome the bonding strength between filaments and matrix. At the ultimate state, the loading capacity increases by 15 % and 17 % for 0.15 % and 0.3 % of basalt fibers and by 10 % and 12 % for 0.45% and 0.6% of basalt fiber. The 0.75 % decreased compressive strength by about 6 % but raised the column’s ultimate load by 18 %. Therefore, basalt fiber benefits the cracking load more than the maximum load. The finite element showed approaching the peak load in numerical and experimental results. The longitudinal rebars and ties do not yield at the ultimate state. Increasing the reinforcement ratio raises loading capacity while lowering the yield stress of bars minimizes the maximum load.